2021
DOI: 10.1128/mbio.03633-20
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System (CNS) Viral Seeding by Mature Monocytes and Potential Therapies To Reduce CNS Viral Reservoirs in the cART Era

Abstract: The human immunodeficiency virus (HIV) enters the central nervous system (CNS) within a few days after primary infection, establishing viral reservoirs that persist even with combined antiretroviral therapy (cART). We show that monocytes from people living with HIV (PLWH) on suppressive cART harboring integrated HIV, viral mRNA, and/or viral proteins preferentially transmigrate across the blood-brain barrier (BBB) to CCL2 and are significantly enriched post-transmigration, and even more highly enriched posttra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 63 publications
(90 reference statements)
3
38
0
1
Order By: Relevance
“…CSF NfL also exhibited this strong linear trend, and these two macrophage biomarkers were among those that correlated well with CSF NfL, along with CSF sCD14 and sVCAM-1. These associations are consistent with the prevalent hypothesis that HIV-1-related neuronal injury is associated with macrophage recruitment into and activation within the CNS [ 31 , 88 , 89 ]. If elevation of these monocyte-associated biomarkers is involved in ‘low-inflammatory’ CNS injury, this begins to increase in frequency when CD4+ cells fall below 200 per μL, Myeloid cells are important in supporting recruitment and replication of M-tropic HIV-1 within the CNS [ 90 93 ] and in generation of neuropathogenic signals and toxins [ 60 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…CSF NfL also exhibited this strong linear trend, and these two macrophage biomarkers were among those that correlated well with CSF NfL, along with CSF sCD14 and sVCAM-1. These associations are consistent with the prevalent hypothesis that HIV-1-related neuronal injury is associated with macrophage recruitment into and activation within the CNS [ 31 , 88 , 89 ]. If elevation of these monocyte-associated biomarkers is involved in ‘low-inflammatory’ CNS injury, this begins to increase in frequency when CD4+ cells fall below 200 per μL, Myeloid cells are important in supporting recruitment and replication of M-tropic HIV-1 within the CNS [ 90 93 ] and in generation of neuropathogenic signals and toxins [ 60 ].…”
Section: Resultssupporting
confidence: 90%
“…CSF NfL also exhibited this strong linear trend, and these two macrophage biomarkers were among those that correlated well with CSF NfL, along with CSF sCD14 and sVCAM-1. These associations are consistent with the prevalent hypothesis that HIV-1-related neuronal injury is associated with macrophage recruitment into and activation within the CNS [31,88,89]. If elevation of these monocyte-associated The panels graph group values for each of the Inflammatory biomarkers in CSF and blood after the subjects were regrouped on the basis of blood CD4+ T cell counts, CSF NfL and HAD diagnosis as described in the text.…”
Section: Model Of Evolving Cns Inflammation and The Three Pathogenic Vectorssupporting
confidence: 80%
“…Uninfected MDM were untreated (Untx) or treated with 100 nM morphine (Sigma-Aldrich, St. Louis, MO, USA), an ART cocktail consisting of 15 μM tenofovir, 15 μM emtricitabine, and 1 μM raltegravir, or both morphine+ART, for 24 h. All three ART drugs were used in their free base forms. Tenofovir and emtricitabine concentrations are consistent with prior studies in primary human macrophages and monocytes [ 36 , 37 , 38 , 39 ]. The concentration of raltegravir used is consistent with studies that tested integrase inhibitors in myeloid cells, and it is within the range detectable in serum [ 40 , 41 ].…”
Section: Methodssupporting
confidence: 87%
“…Except for those functions of metalloproteinase in the previous content, Williams et al found that CD14 + CD16 + monocytes selectively transmigrated across the BBB model due to increased JAM-A and ALCAM expression in HIV-infected individuals ( Williams et al, 2013 ; Williams et al, 2015 ). HIV+ CD14 + CD16 + ART-treated monocytes (mature monocytes infected with HIV and treated with ART) preferentially transmigrate across the BBB to CCL2, which was reduced and/or blocked by blocking antibodies against junctional proteins JAM-A significantly ( León-Rivera et al, 2021 ). In addition, buprenorphine limits the chemokine (C–C motif) ligand 2 (CCL2)-mediated monocyte transmigration into the central nervous system (CNS), through decreasing the phosphorylation of the junctional protein JAM-A increase ( Carvallo et al, 2015 ).…”
Section: Immune Cellsmentioning
confidence: 99%